Environmentally Friendly Small-Sized Water Treatment Plant - Bakhrievich, Alladustov Ulugmurat (European Journal of Life Safety and Stability (2660-9630), 2022)
Based on the analysis of the current development of small water supply systems in the CIS countries and abroad, as well as experimental studies of electrochemical coagulation and thin-layer water clarification during the preliminary preparation of the suspension at the mixing and flocculation chamber, a new technological scheme for water treatment and the design of a small-sized water treatment plant were developed. To assess the technological and economic effect of water treatment and to obtain the operational characteristics of the proposed water treatment plant, production studies of its prototype were carried out. Industrial tests of a prototype of the proposed plant showed a high cleaning effect and reliability of their performance in operation